A Decision-making Model for Third-Party Logistics (3PL) Provider Selection - Jovčić, Stefan (Univerzita Pardubice, 2021)
The issues such as globalization, fast-changing markets, quality of service, more and more demanding customers, and many others, present some of the crucial challenges of the supply chain for enterprises and organizations. Given the fact that supply chains are becoming more complex and extensive, it becomes difficult for the company to organize its activities independently to end-users. Therefore, the cooperation between participants in supply chains is of huge importance. Proper selection of partners in the initial phase of the supply chain is an essential issue for both the company and its customers. This dissertation proposes a decision-making tool for the selection of the company?s collaboration partner ? a 3PL service provider. The qualitative and quantitative criteria are taken into consideration and the author interviewed more than 15 experts from the logistics and supply chain field. The first part of the dissertation addresses an issue about the need for 3PL service providers. In other words, it is necessary to help the company decide about the need for 3PL service providers. The second part relates to the 3PL service provider evaluation. Namely, the experts from the field, as well as an extensive review of the literature help the author of this dissertation decide about the identification as well as evaluation of criteria. The third part, where the main contribution may be found, is oriented to the 3PL service provider selection, by suggesting a decision-making tool. The decision-making tool uses a combination of multi-criteria analysis methods with fuzzy logic. In the beginning, to select the distribution concept, the ARAS multi-criteria analysis method is used. Company considers two possible alternatives. Alternative 1: the distribution concept using its transport fleet and Alternative 2: the distribution concept using 3PL service providers. To identify as well as assess the criteria and alternatives, the experts? opinions are taken into consideration. This is an important issue for companies who need to decide whether to engage 3PL or to do business by themselves. For the case when alternative 2 is a better solution, further continuation of the methodology proposed is to show how to identify the criteria for 3PL selection (in the second phase), how to evaluate them, and what methods to use in the 3PL selection. Experts? opinions as well as an extensive review of the literature was helpful to identify and evaluate the criteria for 3PL selection. A multi-criteria analysis method (such as AHP) combined with fuzzy logic was used to determine the criteria importance. The obtained criteria weights are used in further multi-criteria analysis method such as TOPSIS, to rank the best 3PL service provider among 25 of them. Since no complete data were available to create a real-life case study, given the time constraints of this research, some hypothetical data are used within this dissertation. The experts confirmed that the input data generated by the author of the dissertation, were close to the real conditions on the market and could be used in the illustrative example form. Finally, a decision-making tool is proposed based on fuzzy logic. The inputs are previously identified criteria (from the second phase) and the outputs are the preferences obtained by the TOPSIS. To obtain the fuzzy rule base, Wang-Mendel?s method is applied. The proposed tool is particularly suitable for the implementation when there is no concrete numerical input data about the criteria, but they are given descriptively, throughout the linguistic statements. Therefore, the fuzzy logic system was set up based on the outputs from the TOPSIS method. The TOPSIS method may be used only when the values are known and crisp, while the proposed model is suitable when the values are given between the intervals and in the case of crisp values.
Keywords: logistics; 3PL service providers; outsourcing; Multi-Criteria Decision-Making (MCDM); fuzzy-logic; Wang-Mendel; ARAS